which product equals 3t-12? 4(t-3) 3(t-4) (4-t)3 (3-t)4
Follow Math Help Forum on Facebook and Google+
Originally Posted by dianna which product equals 3t-12? 4(t-3) 3(t-4) (4-t)3 (3-t)4 Hello, dianna, you have to multiply each summand in the bracket by the factor outside the bracket: 4(t-3) = 4t - 4*3 = 4t - 12 3(t-4) = 3*t - 3*4 = 3t - 12 (4-t)3 = 4*3 - t*3 = 12 - 3t (3-t)4 = 3*4 - t*4 = 12 - 4t Now you have the choice EB
Originally Posted by dianna which product equals 3t-12? 4(t-3) 3(t-4) (4-t)3 (3-t)4 Not necessary to break the brackets for each one, just factorice 3t - 12, which yields 3(t - 4), then it's done...
View Tag Cloud